RC4 Cryptography Implementation Analysis on Text Data - Irawan, Agung Susilo Yuda; Pratama, Adi Rizky; Antono, Ryan (JURNAL SISFOTEK GLOBAL, 2021)
Security and confidentiality have become very important and continue to grow. In recent years, there have been several cases involving data security, such as the leaking of Facebook user account information. This is certainly a significant issue in the world of information technology and even the world of entrepreneurship because it involves one of the young entrepreneurs, Mark Zuckerberg. Main problem in this case is data security. who can know information and who should not know information. To overcome such things, research is made in the field of data and information security by analyzing one of the encryption and decryption techniques, namely RC4 cryptography. This study explains how RC4 cryptography works, the advantages and disadvantages of RC4 cryptography, and the effectiveness of RC4 cryptography. RC4 (River Ciper 4) is a decryption encryption technique that uses a key as a reference. The process consists of KSA, PRGA, and XOR. To find out the usefulness of RC4 cryptography, in this study, encryption and decryption were carried out on text data. There are several advantages and disadvantages to RC4 cryptography from a technical point of view. The advantage that needs to be underlined is that this RC4 cryptography uses a certain key as a reference, things like this can provide convenience to the encryption maker but can also be a threat. as a result RC4 can hide information very well while the secret key is not known by others. In addition to being used in text data, this cryptography may be used for other data such as audio and video.